Problem-Solving Skills Viewed from Students’ Learning Style in Problem-Based Learning Assisted by Assemblr Based Javanese Culture Augmented Reality - Firdha Dwi Lestari; Detalia Noriza Munahefi (Indonesian Journal of Mathematics Education, 2023)
Problem-solving skills are one of the core skills in mathematics learning; this skill helps the student be an effective problem solver. Conditions in the field show that the problem-solving skills of Indonesian students are currently low. This study aims to know the improvement of problem-solving skills and the description of that skill in terms of learning styles in problem-based learning assisted by Assemblr based on Javanese culture augmented reality. The research method used was a mixed method with a sequential explanatory strategy. Data collection techniques included tests, questionnaires, and interviews. Quantitative data were analyzed through statistical tests and groupings of student learning styles. Qualitative data analysis was carried out through data collection, reduction, presentation, conclusions, and triangulation techniques. This study used a one-group pretest-posttest design with a random sampling technique, and research subjects was selected by purposive sampling based on learning styles. Results show that there are no students with an auditory learning style. Students’ problem-solving skills increased with the n-gain score, which is 0.5 in the moderate category. In terms of learning styles based on Polya’s stages, show that students' problem-solving skills with visual, kinesthetic, and visual-kinesthetic styles are quite good. Students can understand problems, formulate problem-solving plans, and carry out formulations, but students with visual and kinesthetic learning styles are still not careful in calculations and re-checking answers, while students with visual-kinesthetic learning styles do not re-check their answers. Further research is expected to examine all learning styles, including auditory learning styles.